Control over one's life during the Covid epidemic - Mandič, Srna (Teorija in praksa, 2021)
We examined the changing sense of control over one's life during epidemics. Using original survey data during the first lockdown in May 2020 our case study focuses on Ljubljana%s multi-apartment buildings (MAB) which, due to the physical proximity of the residents and the common spaces/facilities represent a distinct case with its particular threats (infection spread) and potential resources (neighbourly support) for coping with epidemic-related problems. We found a dramatic drop in perceived control over one%s life, from 75% of respondents in usual times to 35% during the pandemic. Accounting for a range of epidemic-associated occurrences in the building and among the residents our regression analysis shows their significant impact on residents% sense of control that highly exceeding those of the quality of life and of basic socio-demographic characteristics. While our case study demonstrates that the specific setting of an MAB can provide a valuable layer of human action in times of crisis, further research is needed to permit generalisations.
Keywords: Blaginja; Covid-19; Epidemics; Epidemije; Everyday life; nadzor nad svojim življenjem; ontološka varnost; večstanovanjske stavbe; Vsakdanje življenje; Welfare